Buddhist views in the prose of V.O. Pelevin - Ayupov T.R. (Genius Journals, 2022)
In this article, the author reviews the influence of Eastern philosophy from various schools, as well as the doctrines of religious Buddhism, which are encountered quite often in early Pelevin's prose. In particular, the early works of V. Pelevin's novels are considered. The novels "Omon Ra", "Chapaev and the Void", "The Life of Insects", "The Caretaker", "Generation P", "Batman Apollo", "The Sacred Book of the Werewolf", "Love for Three Zuckerbrins". The stories "Yellow Arrow", "The Hermit and the Six-fingered".
Keywords: Postmodernism; intertext; V. Pelevin; buddhism